2005
DOI: 10.1097/01.brs.0000174115.58954.17
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of an Educational Intervention to Prevent the Chronic Pain of Whiplash Associated Disorders Following Rear-End Motor Vehicle Collisions

Abstract: The presence of persistent WAD symptoms following simple rear-end MVCs was high in this sample. The video group demonstrated a trend toward less severe WAD symptoms. We recommend evaluating other educational interventions that could reduce WAD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 14 publications
0
32
0
1
Order By: Relevance
“…35 In people with acute whiplash injury, one large randomized controlled study performed in 405 patients who presented to the emergency department found that an educational video added to usual care resulted in a 7.9% (95% confidence interval −2.0 to 17.8) decrease in the proportion of people who still had pain at 24 weeks compared with usual care alone. 36 Fig 1 | The biopsychosocial model of pain posits that biological, psychological, and social factors influence who develops chronic pain (pink circles) and that chronic pain has biological, psychological, and social consequences (blue circles 45 In an MRI study of 78 patients with cervical radiculopathy for less than one month, the clinically affected root was identified in 73% of patients. 46 However, the false positive rate was 45% and the false negative rate was about 26%, indicating the absence of compression at the affected level.…”
mentioning
confidence: 99%
“…35 In people with acute whiplash injury, one large randomized controlled study performed in 405 patients who presented to the emergency department found that an educational video added to usual care resulted in a 7.9% (95% confidence interval −2.0 to 17.8) decrease in the proportion of people who still had pain at 24 weeks compared with usual care alone. 36 Fig 1 | The biopsychosocial model of pain posits that biological, psychological, and social factors influence who develops chronic pain (pink circles) and that chronic pain has biological, psychological, and social consequences (blue circles 45 In an MRI study of 78 patients with cervical radiculopathy for less than one month, the clinically affected root was identified in 73% of patients. 46 However, the false positive rate was 45% and the false negative rate was about 26%, indicating the absence of compression at the affected level.…”
mentioning
confidence: 99%
“…Unfortunately, specific management strategies aimed at preventing the development of chronic pain remain speculative and have been mainly restricted to behavioral approaches. 12,31,130 However, recent evidence points to more favorable outcomes (reduction in pain and disability) when employing a multimodal physiotherapy program addressing the specific impairments compared to a self-management behavioral approach for chronic WAD. 58 The effects, however, are mitigated in the presence of abnormal sensory features known to have prognostic value (eg, cold hyperalgesia and widespread allodynia).…”
mentioning
confidence: 99%
“…Several studies suggest that this may be an important intervention for patients with elevated levels of catastrophizing [8,17,42,43]. Reassurance and activity encouragement is another brief intervention [42,44], which has been shown to reduce a number of variables associated with catastrophizing, including pain intensity, pain-related fear, and disability [45][46][47]. Moseley et al have found significant reductions on catastrophizing following a single neurophysiological educational session [10].…”
Section: Discussionmentioning
confidence: 99%